Furanocoumarin Content, Antioxidant Activity, and Inhibitory Potential of Heracleum verticillatum, Heracleum sibiricum, Heracleum angustisectum, and Heracleum ternatum Extracts against Enzymes Involved in Alzheimer's Disease and Type II Diabetes. Issue 4 (28th March 2019) - Ozek, Gulmira; Yur, Suleyman; Goger, Fatih; Ozek, Temel; Andjelkovic, Boban; Godjevac, Dejan; Sofrenic, Ivana; Aneva, Ina; Todorova, Milka; Trendafilova, Antoaneta
Abstract: Hexane extracts of Heracleum verticillatum, H. sibiricum, H. angustisectum, and H. ternatum were studied for their furanocoumarin content antioxidant potential and acetylcholinesterase and α ‐amylase inhibitory activities. Quantification of the furanocoumarins was performed by 1 H‐NMR. Pimpinellin was found to be the main component in the roots of all studied species. Bergapten and imperatorin were the major compounds in the fruits of H. sibiricum and H. verticillatum, respectively, while byakangelicol dominated in H. angustisectum and H. ternatum fruits. The leaf and fruit extracts of H. angustisectum demonstrated the highest DPPH radical scavenging activity and TEAC (IC50 0.58 mg/mL and 1.83 mm, respectively). The root extracts of H. verticillatum and H. angustisectum were found to be the most effective against acetylcholinesterase (IC50 0.30 and 0.34 mg/mL, respectively). The studied extracts were not active or demonstrated a weak inhibitory effect (%Inh. up to 29.7) towards α ‐amylase. Abstract :